Entrepreneur’s the Perceptions of Institutional Uncertainty and the Constitutional Process - Duarte Valdivia, Diego; Muñoz Cisterna, Víctor; Castillo Vergara, Mauricio; Llanos Millar, Catalina (Revista del CLAD Reforma y Democracia, 2023)
Entrepreneurs are familiar with uncertainty and risk, that is, their nature is to tolerate situations in which it is not possible to accurately anticipate or predict the future. However, the constitutional process that Chile experienced during the years 2020 to 2022 has exposed them to a different type of uncertainty that affects them differently depending on gender. This exploratory research aims to analyze how this process has generated such uncertainty and affected the perceptions of entrepreneurs, especially in relation to the changes proposed in the new constitution. The study sample includes entrepreneurs and SME executives, with a special focus on gender differences and perceptions of institutional uncertainty. The main results reveal that the constitutional process has generated concern and uncertainty among entrepreneurs, especially due to the proposed changes in social and economic rights. A greater susceptibility among female entrepreneurs stands out, which can be explained by domestic obligations and gender barriers in access to resources. Furthermore, a decrease in confidence and perception of stability in the business environment is observed, especially during the period of constitutional debate. The results of this research can help the evidence-based dialogue between the public and private sectors regarding the effects that uncertainty arising from institutional change processes has on entrepreneurship and entrepreneurs’ decisions.
Keywords: Entrepreneurship; Institutional Uncertainty; Constitutional Process; Gender